Turk J Anaesthesiol Reanim 2021
DOI: 10.5152/tjar.2021.21370
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine Supplementation for the Prevention of Postoperative Liver Dysfunction after On-Pump Cardiac Surgery

Abstract: Background: Incidence of postoperative liver dysfunction continues to be high (ranging from 10 to 35%) in those who underwent cardiac surgeries using cardiopulmonary bypass (CPB) and is associated with considerable morbidity and mortality. Prolonged cardiopulmonary bypass time (CPBT) was found to be an independent predictor of postoperative liver dysfunction. So, the aim of this study was to evaluate the effect of prophylactic use of N -acetylcysteine (NAC) in patients undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In another rat model of CPB, N-acetylcysteine was shown to ameliorate CPB-associated intestinal injury via reduction in inflammation and oxidative stress as measured by decreased levels of intestinal malondialdehyde, TNF-α, IL-6, and serum diamine oxidase ( 336 ). A number of studies have recently shown N-acetylcysteine to improve pulmonary, hepatic, and renal outcomes in patients undergoing CPB with and without preexisting pulmonary and renal insufficiency ( 337 342 ).…”
Section: Strategies To Modulate Cpb-associated Inflammatory Responsementioning
confidence: 99%
“…In another rat model of CPB, N-acetylcysteine was shown to ameliorate CPB-associated intestinal injury via reduction in inflammation and oxidative stress as measured by decreased levels of intestinal malondialdehyde, TNF-α, IL-6, and serum diamine oxidase ( 336 ). A number of studies have recently shown N-acetylcysteine to improve pulmonary, hepatic, and renal outcomes in patients undergoing CPB with and without preexisting pulmonary and renal insufficiency ( 337 342 ).…”
Section: Strategies To Modulate Cpb-associated Inflammatory Responsementioning
confidence: 99%
“…There are considerable biochemical changes during and after the CPB, such as oxygenation in non-endothelial membranes, reperfusion damage, absorption of nutrients in the CPB circuit [91,92]. This context of inflammation and oxidative stress has been associated with postoperative complications in these patients, such as atrial fibrillation, acute kidney and lung and liver injury [12,51,[93][94][95]. In this sense, several drugs with antioxidant properties are being investigated, either as individual therapies or in combined treatment to reduced oxidative damage.…”
Section: Future Perspective and Antioxidant Agentsmentioning
confidence: 99%
“…In addition, NAC has exhibited important effects by reducing the levels of lactate and nitrogenous slags in the blood 24 h after cardiac surgery with CPB, suggesting a beneficial effect on peripheral and renal tissue perfusion [123]. Furthermore, the prophylactic use of NAC attenuates the liver damage induced by cardiopulmonary bypass during cardiac surgery, in addition to reducing the incidence of acute kidney injury in this type of surgery [93,[124][125][126]. However, more clinical studies are needed to standardize necessary doses and treatment times, as well as monitoring possible unwanted effects.…”
Section: N-acetylcysteinementioning
confidence: 99%